Healthcare Access - New Threats, New Approaches 2023
DOI: 10.5772/intechopen.107418
|View full text |Cite
|
Sign up to set email alerts
|

Funding of Oncology Benefits by Medical Schemes, South Africa: A Focus on Breast and Cervical Cancer

Abstract: Breast and cervical cancers are among the top five worldwide. Over half of untreated breast cancer patients die, compared to nearly 90% of cervical cancer patients. Early breast and cervical cancer screening can reduce mortality risk. This study examined breast and cervical cancer rates among South African medical scheme members. The study’s secondary goal was to analyse how medical schemes funded these two cancers, including patient and/or out of pocket payments, to identify funding gaps. The study was a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…25 From a recent study on funding health care benefits by medical schemes, approximately 511 ophthalmologists claim from medical schemes. 26 The latter provide further credence to the statistic indicating that the private sector employs 85% of active ophthalmologists (again, distribution is skewed to the private sector).…”
Section: Ophthalmologistsmentioning
confidence: 76%
See 4 more Smart Citations
“…25 From a recent study on funding health care benefits by medical schemes, approximately 511 ophthalmologists claim from medical schemes. 26 The latter provide further credence to the statistic indicating that the private sector employs 85% of active ophthalmologists (again, distribution is skewed to the private sector).…”
Section: Ophthalmologistsmentioning
confidence: 76%
“…Similarly, with ophthalmology, a study by Majola 20 confirmed that more than 593 ophthalmologists registered, while Willie found 511 claiming ophthalmologists from medical schemes. 26 The analysis showed that the geographic distribution of claiming optometrists was relative to the distribution of members other than Mpumalanga and KwaZulu-Natal provinces. Provinces such as the Gauteng and North West had an undersupply of optometrists relative to the covered population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations